Introduction of mini-Clinical Evaluation Exercise as a mode of assessment for postgraduate students in medicine for examination of sacroiliac joints - Anuj Singhal; Shankar Subramanian; Sonal Singh; Arun Kumar Yadav; Anup Hallapanavar; B Anjali (Indian Journal of Rheumatology)
Background: Formative and subjective assessment of medical education is the need of the hour today. Mini-Clinical Evaluation Exercise (mini-CEX) and Directly Observed Procedural Skills (DOPS) are the commonly used workplace-based assessment (WPBA) tools which have been extensively studied in both undergraduate and postgraduate (PG) settings. In this study, we tried to assess the feasibility of mini-CEX and also its acceptability among PG students of internal medicine and teaching faculty for the examination of sacroiliac joints. Methods: This is an interventional study which was carried out in a government medical college in Pune, Maharashtra, India, from January to June 2019. A total of 18 1st- and 2nd-year PG students and 9 teaching faculty from the department of internal medicine participated in this study. Each student underwent five mini-CEX evaluations over a period of 6 months under different teaching faculty. Feedback was taken from both the teaching faculty and students regarding the feasibility of mini-CEX as an assessment tool. Results: A total of ninety mini-CEX exposures involving 18 PG students and nine faculty were analyzed. We found a statistically significant improvement in the domain of medical interviewing (P < 0.001), physical examination (P = 0.003), professionalism (P = 0.001), clinical judgment (P = 0.003), counseling skills (P < 0.001), and organizing efficiency (P < 0.001). Overall clinical competence improved from a scale of 5 (1.7) to 6.7 (0.8). Conclusion: The results of this study show that overall mini-CEX is an acceptable and effective assessment tool. However, regular training of assessors through workshops on the provision of effective feedback is required. Modification of the assessment form based on the feedbacks provided by teachers and students will further facilitate the implementation of this teaching tool in the curriculum.